2015
DOI: 10.1007/s12282-015-0622-y
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-infiltrating CD45RO+ memory cells are associated with a favorable prognosis breast cancer

Abstract: These results suggested that CD45RO(+) effector cells may both help eradicate local tumors and prevent metastases to the lymphatic systems in breast cancer patients. High ratio of CD45RO expressing TILs was associated with recurrence-free survival improvement and a trend toward cancer-specific survival improvement in breast cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 26 publications
0
18
1
Order By: Relevance
“…Additionally, in other studies, CD3 + and CD45RO + TILs were significantly correlated with clinico-pathological features [39,40]. However, in our study, no significant correlation was observed, except for CD3 + and lymph node metastasis, this may be further explored in a larger patient cohort.…”
Section: Discussioncontrasting
confidence: 62%
“…Additionally, in other studies, CD3 + and CD45RO + TILs were significantly correlated with clinico-pathological features [39,40]. However, in our study, no significant correlation was observed, except for CD3 + and lymph node metastasis, this may be further explored in a larger patient cohort.…”
Section: Discussioncontrasting
confidence: 62%
“…There is a general consensus that in the context of the antitumor immune response, the frequency of CD8 + lymphocytes and their memory T cell subsets correlates positively with smaller tumor size, lower disease stages, less lymph node involvement, and a generally better prognosis or survival in most types of cancer, e.g. breast carcinoma [14,[16][17][18][19][20][21][22]. CD8 + lymphocytes are assumed to mediate tumor rejection through the direct killing of transformed cells.…”
Section: Discussionmentioning
confidence: 99%
“…These studies indicate the anti-tumor effect of CD45RO + T cells. In addition, CD45RO + TILs are negatively correlated with tumor size, lymph nodes metastasis in breast cancer patients (27), associated with lesser advanced T stage and TNM stage in rectal cancer (28), and correlated with well differentiation and lower TNM stage in renal cell carcinoma (29). Consistent with previous studies, we found that CD45RO expression was increased in lung adenocarcinoma tissues compared to paired adjacent lung tissues, and CD45RO + TILs were negatively correlated with tumor size, lymph node metastasis and TNM stage in lung adenocarcinoma patients.…”
Section: Analysis Of Baseline Factors Affecting Osmentioning
confidence: 99%